Peningkatan Kinerja Pengamanan di Bandara El-Tari Kupang - Dina Yuliana (WARTA ARDHIA, 2010)
Research of improvement airport security performance takes survey at El Tari Airport — Kupang has been implemented. The purpose of the study was to assess the level of security services and know the perception of air transport passengers in the El Tari Airport – Kupang on the security services provided by the airport operator (PT Angkasa pura I). The results of the research found that by using gap analysis can be known 5 (five) in order to prioritize security improvements at the El Tari Airport – Kupang, namely ease of luggage document processing procedures at the airport, the adequacy of the amount of equipment used for baggage inspection at airports, the attitude of the security officer in providing service, convenience checks of passengers and goods at airports and behaviors, skills, and skills of security. Quadrant analysis (importance and performance) shows the attributes that need attention and necessary efforts to repair the attitude of the security officer in poviding services and behavior, skill and ability of the baggage document at the airport.